REFORMULATION OF CRIMINAL LIABILITY CONCEPT IN CRIMINAL ACT OF CORRUPTION IN INDONESIA BASED ON PANCASILA - HERLAMBANG HERLAMBANG (Universitas Bengkulu, 2016)
AbstractThe successful action of eradicating corruption in Indonesia is influenced by the accuracy of formulating the Criminal liability concept of corruptors. Accuracy is needed in determining corruptor to convict those who take part in corruption cases so they can be responsible for their corruptions and be punished according to the regulation applied. This study used an empirical legal research methodology, composing into an article from several research reports. The current concept of criminal liability seems inadequate to arrest the doer that takes part in corruption which has been executed for his criminal responsibility. This indicates the discrimination in sentencing the corruptors. Different from regulation to charge doer in general crimes, a corruptor is charged based on the concept of individual responsibility, thus it is necessary to propose another responsibility which is developed based on Adat Law such as collectivity principle of responsibility